مكانة الوسيط القضائي في تفعيل الوساطة لتسوية النزاع الإداري - حمدادو، محمد الأمين Hamdadou, Mohammed Alamin (المركز الجامعي بتندوف, 2020)
تعتبر الوساطة الأساس الذي يقوم عليه نظام الطرق البديلة لحل المنازعات، ويعتبر الوسيط أهم حلقة في تسوية هذا النزاع عن طريق نظام الوساطة القضائية، وتكمن أهمية هذا البحث في بيان دور ومكانة الوسيط القضائي في تفعيل الوساطة لتسوية النزاع الإداري، كما أعطى له مكانة وذلك بالقيام بدورين رئيسيين لتحقيق التسوية وفض النزاع بين أطرافه؛ فأما الأول فيتمثل في تقريب وجهات النظر من خلال اختيار الإجراءات التي تتناسب مع القضية المطروحة، وتحوز على قبول أطراف النزاع الإداري، أما العامل الثاني فيتمثل في التوفيق بين أطراف النزاع الإداري ومساعدتهم على التوصل إلى تسوية ودية من خلال إرشادهم إلى النقاش البناء، وتنمية التواصل والتفاهم بينهم، وتقديم اقتراحات غير ملزمة يرى أنها تساعدهم على التوصل إلى تسوية ودية عادلة للنزاع القائم بينهم.
Mediation is the basis on which the alternative dispute resolution system is based, and the mediator is the most important link in settling this dispute through the judicial mediation system, and the importance of this research lies in showing the role and position of the judicial mediator in activating mediation to settle the administrative dispute, and it also gave him a position by playing two roles Two main parties to achieve settlement and settle the dispute between the parties; As for the first, it is to bring points of view closer by choosing the procedures that are appropriate to the issue at hand and have the acceptance of the parties to the administrative dispute, while the second factor is to reconcile the parties to the administrative dispute and help them reach an amicable settlement by guiding them to constructive discussion and developing communication and understanding. Between them, and submitting non-binding proposals that he believes will help them reach an amicable and just settlement of the dispute between them.
Keywords: الوساطة القضائية -- النزاعات الإدارية -- تسوية النزاعات